Smart borders, digital identity and big data: how surveillance technologies are used against migrants - Korkmaz, Emre Eren (Bristol University Press, 2024)
In recent years, UN agencies, global tech corporations, states and humanitarian NGOs have invested in surveillance technologies to support migrant communities and streamline their management. This book reveals the way in which they grant extensive powers to states and big tech corporations to control communities